2005
DOI: 10.1007/s10705-004-0382-0
|View full text |Cite
|
Sign up to set email alerts
|

The variation of greenhouse gas emissions from soils of various land-use/cover types in Jambi province, Indonesia

Abstract: We measured fluxes of three greenhouse gases (N 2 O, CO 2 and CH 4 ) from soils of six different land-use types at 27 temporary field sites in Jambi Province, Sumatra, Indonesia. Study sites included natural and logged-over forests; rubber plantation; oil palm plantation; cinnamon plantation; and grassland field. The ranges of N 2 O, CO 2 and CH 4 fluxes were 0.13-55.8 µg N m −2 h −1 ; 1.38-5.16 g C m −2 d −1 ; −1.27-1.18 mg C m −2 d −1 , respectively. The averages of N 2 O, CO 2 and CH 4 fluxes at 27 sites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 28 publications
(49 reference statements)
12
52
3
Order By: Relevance
“…Annual CH 4 uptake rates under field conditions at the 2,000 and 3,000 m sites were comparable to those reported for tropical montane forest soils at comparable elevation in Indonesia (1.5 and 3.3 kg CH 4 -C ha -1 year -1 ) (Ishizuka et al 2005;Purbopuspito et al 2006). Annual CH 4 fluxes at the 1,000 m site were larger than previously reported for other premontane forests in Africa (Delmas et al 1992), Australia (Kiese et al 2008), Indonesia (Purbopuspito et al 2006) and China (Werner et al 2006) and were also larger than those reported from lowland forests in Costa Rica (Keller and Reiners 1994;Reiners et al 1998) and Brazil (Keller et al 2005).…”
Section: Net Exchange Of Ch 4 Under Field Conditionssupporting
confidence: 79%
See 1 more Smart Citation
“…Annual CH 4 uptake rates under field conditions at the 2,000 and 3,000 m sites were comparable to those reported for tropical montane forest soils at comparable elevation in Indonesia (1.5 and 3.3 kg CH 4 -C ha -1 year -1 ) (Ishizuka et al 2005;Purbopuspito et al 2006). Annual CH 4 fluxes at the 1,000 m site were larger than previously reported for other premontane forests in Africa (Delmas et al 1992), Australia (Kiese et al 2008), Indonesia (Purbopuspito et al 2006) and China (Werner et al 2006) and were also larger than those reported from lowland forests in Costa Rica (Keller and Reiners 1994;Reiners et al 1998) and Brazil (Keller et al 2005).…”
Section: Net Exchange Of Ch 4 Under Field Conditionssupporting
confidence: 79%
“…Uptake of atmospheric CH 4 in aerobic tropical forest soils is estimated to account for about 28% of the global annual soil consumption (6.2 Tg year -1 ) (Dutaur and Verchot 2007). Montane forests cover about 9% of the tropics (FRA 2000) and the few studies that have been conducted on CH 4 fluxes show that their soils are generally CH 4 sinks (Delmas et al 1992;Ishizuka et al 2005;Kiese et al 2008;Purbopuspito et al 2006). However, a recent study conducted by our group in the same region as the present study showed that CH 4 produced in the canopy by Bromeliads may change the source-sink balance of these ecosystems (Martinson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Annual N 2 O emissions from acacia plantation soils were 2.56 kg N ha À1 , eight times greater than those from secondary forest [Ishizuka et al, 2002[Ishizuka et al, , 2005aVerchot et al, 2006]. Thus N 2 O flux from grasslands is likely lower than that from acacia plantations.…”
Section: Conversion To Acacia Plantations Might Boost N 2 O Flux Frommentioning
confidence: 96%
“…These low secondary forest emissions are comparable to those observed at primary forests in central Sumatra (0.13 kg N ha À1 and 0.39 kg N ha À1 [Ishizuka et al, 2002]), but relatively low compared to emissions from southern Sumatra forests (1.47 and 1.80 kg N ha À1 at sites showing high WFPS (90 -100% [Verchot et al, 2006]) and montane forests in central Sulawesi (0.29, 1.01, and 1.11 kg N ha À1 [Purbopuspito et al, 2006]). Ishizuka et al [2005a] suggested that even within a limited geographical region, N 2 O flux in soils having a udic moisture regime is higher than that in drier soils. Thus the relatively higher N 2 O flux observed by Verchot et al [2006] may be at least partly site specific and reflect exceptionally wet soil moisture conditions.…”
Section: Conversion To Acacia Plantations Might Boost N 2 O Flux Frommentioning
confidence: 99%
“…Although Sumatra, Indonesia, represents a hot spot of land-use change, especially for the establishment of rubber and oil palm plantations, how this affects soil CO 2 and CH 4 fluxes remains highly uncertain for the following reasons: (1) most studies relating land-use change to trace gas emissions have been conducted in South and Central America (Keller and Reiners, 1994;Davidson et al, 2000;Veldkamp et al, 2001;Salimon et al, 2004) and only few studies were conducted in southeast Asia (Ishizuka et al, 2002;Veldkamp et al, 2008); (2) most studies have focused on forest conversion to traditional land-use types, such as maize, pastures, slash-and-burn agriculture, cacao and coffee, and less on the rapidly expanding tree cash crops such as rubber and oil palm; (3) the few studies that reported CO 2 and CH 4 fluxes from oil palm plantations were conducted on peat soils (Melling et al, 2005a, b), whereas the studies conducted on mineral soils, where most of the rubber and oil palm plantations are located, were either conducted without spatial replication, covered only short periods of measurements (Ishizuka et al, 2002;Adachi et al, 2005;Werner et al, 2006) or measured only once (Ishizuka et al, 2005). It is imperative that better information becomes available on trace gas fluxes from these economically important and rapidly expanding rubber and oil palm plantations.…”
Section: E Hassler Et Al: Soil Fertility Controls Soil-atmosphere Cmentioning
confidence: 99%